Prevalence of Sexual Dysfunction in Thai Pregnant Women - Sompop Kuljarusnont; Kusol Russameecharoen; Wiboolphan Thitadilok (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To study the prevalence of sexual dysfunction in Thai pregnant women.Materials and Methods: A descriptive cross-sectional study was conducted among 260 healthy, singleton and third trimester pregnant women, presenting with a stable relationship with their partners, attended at the antenatal care clinic, Department of Obstetrics and Gynaecology, Siriraj Hospital during July 20, 2010 to December 15, 2010. The Female Sexual Function Index (FSFI) questionnaire was used to evaluate the sexual function in each trimester. A total FSFI score of < 26 was interpreted as sexual dysfunction.Results: The mean age of participants was 28.1+5.8 years old. The mean gestational age was 36.9+2.3 weeks. The prevalence of sexual dysfunction was 90.8% (95%CI 86.6% to 93.7%). Those in the first, second and third trimesters were 58.1% (95%CI 52.0% to 63.9%), 61.5% (95%CI 55.5% to 67.2%) and 88.5 % (95%CI 84.0% to 91.8%), respectively. The prevalence of sexual dysfunction increased in accordance with advancing gestational age. Additionally, this study also demonstrated the decreasing of sexual frequency from 3.4+0.9 to 1.3+0.9 times per week along with the 22.7% changing of position during pregnancy period.Conclusion: The prevalence of sexual dysfunction in Thai pregnant women was rather high particularly in the third trimester. Besides the routine antenatal care, the healthcare providers should concern and provide the useful information for this sensitive issue.